Analysis and artificial neural network prediction of melting properties and ideal mole fraction solubility of cocrystals - Gamidi, Rama Krishna; Rasmuson, Ake C. (Crystal Growth & Design, 2020)
Different artificial neural network (ANN) models have been developed and examined for prediction of cocrystal properties based on pure component physical properties only. From the molecular weight, melting temperature, melting enthalpy, and melting entropy of the pure compounds, the corresponding melting properties of the cocrystals and the cocrystal ideal solubility have been successfully predicted. Notably, no information whatsoever about the cocrystals is needed, besides the identification of the two compounds from which the cocrystal is formed. In total, 30 cocrystal systems of 8 different model components, namely, theophylline, piracetam, gabapentin-lactam, tegafur, nicotinamide, salicylic acid, syringic acid, and 4,4'-bipyridine, with distinct coformers have been chosen as the model systems for the construction of ANN models. In all the cases, 70% of the data points have been used to train the model, and the rest were used to test the capability of the model (as a validation set) as selected through a random selection process. The training process was stopped with overall r(2) values above 0.986. In particular, the models capture how the coformer structure influences the targeted physical properties of cocrystals.

Separation of a diastereomeric diol pair using the mechanical properties of crystals - Gamidi, Rama Krishna; Dandawate, Monica; Choudhury, Rahul; Tothadi, Srinu; Nangia, Ashwini; Reddy, D. Srinivasa (Crystengcomm, 2021)
We report the separation of a (2S,3R/S)-3-ethyl-1-phenylhex-5-ene-2,3-diol (ephd) diastereomeric pair with visually indistinguishable acicular morphologies based on their mechanical responses, which is found to be more efficient than conventional separation methods. Furthermore, the molecular crystals of (2S,3R)-ephd show elastic deformation, while (2S,3S)-ephd fractures in a brittle manner under similar conditions.

Transition metal- and oxidant-free regioselective synthesis of 3,4,5-trisubstituted pyrazoles by means of [3+2] cycloaddition reactions - Allaka, Bhargava Sai; Basavoju, Srinivas; Gamidi, Rama Krishna (ChemistrySelect, 2022)
A highly efficient regioselective synthesis of 3,4,5-trisubstituted pyrazoles via transition metal- and oxidant-free, three component [3+2] cycloaddition with thiazolidinedione chalcones, benzaldehydes and N-tosylhydrazine is described. The reaction proceeds through C-C and C-N bond formations under mild reaction conditions to produce structurally diverse polysubstituted pyrazoles in moderate to good yields.
Keywords: 3; 4; 5-trisubstituted pyrazoles; Cycloaddition; Multicomponent reaction; Oxidant free; Regioselectivity; Transition metal free

Ultrasound assisted green protocol for the synthesis of quinoxaline based bisspirooxindoles: crystal structure analysis, enone umpolung, DFT calculations, anti-cancer activity, and molecular docking studies - Baddepuri, Sravanthi; Allaka, Bhargava Sai; Gamidi, Rama Krishna; Faizan, Mohmmad; Pawar, Ravinder; Basavoju, Srinivas (Synthetic Communications, 2023)
A series of novel quinoxaline based bisspirooxindolo-pyrrolizidines were synthesized through 1,3-dipolar cycloaddition under ultrasonication with shorter reaction time and good yields. The compounds were well characterized by various spectroscopic methods and finally single crystal X-ray diffraction method (4c, 4d). DFT energy calculations confirm the regioselectivity due to enone umpolung effect. The in vitro anti-cancer activity of the synthesized compounds (4a-s) shows that the compounds 4g and 4q exhibited good anti-cancer activity with IC50 values14.51 +/- 1.1 and 11.36 +/- 0.23 mu M against DU-145 prostate cancer cell line; and 16.78 +/- 0.95 and 14.28 +/- 0.64 mu M against Hela cervical cancer cell lines when compared to the standard anti-cancer drug doxorubicin (1.75 +/- 0.06 and 1.35 +/- 0.09 mu M). In silico molecular docking studies indicated that the synthesized compounds may serve as a potential lead for the further development of novel anti-cancer agents.
Keywords: Anti-cancer activity; bisspirooxindoles; DFT calculations; Hirshfeld surface; ultrasonication

Cu-catalyzed multicomponent reaction of arylhydrazines with β-ketoesters and TBN: one-pot access to N 2-aryl 1,2,3-triazole-1-oxides - Mujahid, Mohammad; Vara, Vijay; Arshad, Usman; Gamidi, Rama Krishna; Muthukrishnan, M. (Journal of Organic Chemistry, 2024)
We report a copper-catalyzed one-pot, multicomponent strategy for the convenient synthesis of N 2-aryl 1,2,3-triazole-1-oxides using arylhydrazines, beta-ketoesters, and tert-butyl nitrite. This mild and simple reaction proceeds in an atom-economic manner with broad substrate scope, affording a variety of N 2-aryl 1,2,3-triazole-1-oxide derivatives. Other salient features of the reaction are good functional group tolerance, scalability, and product diversification.

Design, synthesis, anti-mycobacterial activity, molecular docking and ADME analysis of spiroquinoxaline-1,2,4-oxadiazoles via [3+2] cycloaddition reaction under ultrasound irradiation - Kanchrana, Madhu; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (MOLECULAR DIVERSITY, 2024)
Keywords: 2; 4-oxadiazoles; cytotoxicity activity; molecular; Mycobacterium tuberculosis; Spiroquinoxaline-1

Ready access to [5,6,5]-Trioxa-spiro and fused ketals via ag-catalyzed cascade annulation of 4-pentyn-1-ols and aldehydes - Vinodkumar, Ramavath; Nakate, Ashwini K.; Gamidi, Rama Krishna; Kontham, Ravindar (Organic Letters, 2024)
In this study, we unveil the versatility of 4-pentyn-1-ols as carbonyl surrogates for the unprecedented synthesis of diverse oxygen heterocycles, including [5,6,5]-bis-spiroketals (trioxadispiroketals) and [5,6,5]-furano-spiroketals related to bioactive natural products. These reactions commence with the pi-activation-induced intramolecular hydroalkoxylation of 4-pentyn-1-ols, yielding cyclic enol ethers, which undergo subsequent three-component annulation with aldehydes in a [2+2+1+1] fashion, resulting in the formation of [5,6,5]-bis-spiroketals. Notably, the distinctive steric features of alkynyl alcohols, particularly those with a secondary or tertiary alcohol functionality, dictate divergent reaction pathways, leading to the formation of [5,6,5]-furano-spiroketals.

Synthesis, crystal growth, physicochemical study of 1,3-dihexyl-2-me-thyl-1H-benzo[d]imidazol-3-ium bromide and in silico nonlinear optical property determination - Siddiqui, Zahir Ali; Gamidi, Rama Krishna; Sekar, Nagaiyan; More, Sandeep (Journal of Molecular Structure, 2024)
This study encompasses the synthesis and characterization of 1,3-dihexyl-2-methyl-1H-benzo[d]imidazol-3-ium bromide (DHBIB) using techniques such as NMR, IR, and HRMS. The study also explores the influence of different solvents, specifically water and acetonitrile, on the growth of single crystals. An intriguing observation is the transformation of crystal packing from orthorhombic to monoclinic when solvent conditions change, illustrating the pivotal role of the cation in controlling the crystal structure of DHBIB salts. The analysis of its electronic properties reveal a deep -lying LUMO (-3.73 eV), suggesting DHBIB's electron -accepting characteristics. Furthermore, the study records absorption maxima ( lambda max ) at 279 nm and 282 nm in various solvents, demonstrating that DHBIB lacks absorption in the visible range (400-800 nm), making it promising for non-linear optical (NLO) applications. Analysis of the natural bond orbital (NBO) stabilization energies 50.87, 42.12, and 45.33 kcal/mol along pi(C3-C4) -> pi*(C6-C8), pi(C3-C4) -> pi*(C10-C12), and pi (C10-C12) -> pi*(C6-C8) reveal a preference for intramolecular charge transfer in DHBIB. Enhanced first and second -order hyperpolarizabilities ( beta ; 13.47x10 -30 esu, gamma ; 75.36x10 - 36 esu) compared to benzimidazole and benzimidazolium salicylate salt further supports its potential for NLO applications.
Keywords: DHBIB; Hyperpolarizability; Monoclinic; NBO; Orthorhombic

Synthesis of quinazolinone based spirocyclopropanes via [3?+?2] cycloaddition reaction: in silico anti-tubercular molecular docking studies and ADME prediction - Allaka, Bhargava Sai; Kanchrana, Madhu; Gamidi, Rama Krishna; Basavoju, Srinivas (Polycyclic Aromatic Compounds, 2024)
A highly efficient cascade annulation approach is developed for the synthesis of novel quinazolinone-based spirocyclopropanes via three-component [3 + 2] cycloaddition reaction with aldehydes, tosylhydrazide and quinazolinyl chalcones. The reaction features the formation of two C–C bonds and three stereogenic centers. A variety of highly functionalized spirocyclopropyl quinazolinones were obtained in good yields under mild reaction conditions. Furthermore, in silico anti-tubercular (anti-TB) molecular docking studies were performed for the generated compounds against three Mycobacterium tuberculosis proteins with PDBID: 1DF7, 1P44 and 4TZK. ADME prediction were evaluated for the drug like properties of the synthesized compounds.

Ultrasound-assisted ionic liquid-mediated green method for synthesis of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidines, their anti-tubercular activity, molecular docking study and ADME predictions - Baddepuri, Sravanthi; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (New Journal of Chemistry, 2024)
The aim of the study is to develop the synthesis of a novel series of potent anti-tubercular (anti-TB) activity of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidine derivatives via an efficient green approach achieved by using an ionic liquid ([Bmim]BF4) under ultrasonication. The title compounds 4a-4ad with a general molecular formula CaHbX(0-2)NcOd (X = F/Cl/Br) were produced with high yields in shorter reaction time and well characterized by using spectral techniques; and finally single crystal X-ray diffraction method (4b). The newly synthesized compounds were evaluated for their in vitro anti-TB activity against Mycobacterium tuberculosis H37Rv strain. Among all, six compounds 4e (C36H29N5O4), 4g (C34H28N4O3), 4q (C36H28F2N4O2), 4r (C36H28ClFN4O2), 4y (C36H29BrN4O2) and 4z (C36H28BrFN4O2) exhibited significant anti-TB activity with MIC value 6.25 mu g mL-1, when compared to the standard drug ethambutol (MIC:1.56 mu g mL-1). In silico molecular docking studies were performed against M. tuberculosis enoyl-acyl carrier protein reductase inhibitor. The compounds 4o, 4p, 4y and 4aa were exhibited least binding energies -12.58, -12.61, -12.58 and -12.57 kcal mol-1, respectively. These results reveal that the produced compounds might be used for the future generation of novel anti-TB drugs. The study aims to develop and synthesis of a novel series of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidine derivatives as potent anti-TB agents via an efficient green approach by using an ionic liquid ([Bmim]BF4) under ultrasonication.

Unraveling the metal-ligand cooperativity in a phosphine-free Mn(II)-catalyzed transfer hydrogenation of nitriles to primary amines and dehydrogenation of dimethylamine borane - Chowdhury, Deep; Gupta, Kriti; Gamidi, Rama Krishna; Jindal, Garima; Mukherjee, Arup (ACS CATALYSIS, 2024)
Keywords: CATALYZED TRANSFER HYDROGENATION; STEREOSELECTIVE TRANSFER SEMIHYDROGENATION

Accessing polysubstituted 2-cyclopentenones via base-mediated annulation of β-keto esters and phenacyl bromides - Kumar, Mohit; Paul, Vincent; Gamidi, Rama Krishna; Senthilkumar, Beeran (Organic & Biomolecular Chemistry, 2025)
A transition metal-free method is demonstrated for the synthesis of polysubstituted 2-cyclopentenone compounds, which involves the direct annulation of phenacyl bromide with beta-keto esters in a single step. This process proceeds through a base-mediated SN2 nucleophilic substitution, followed by an intramolecular aldol condensation, resulting in the formation of three C-C bonds and one ring in a cascade manner. The experimental results achieved a record high yield of highly substituted diverse 2-cyclopentenone analogues, which exhibit very good structural resemblance to biologically significant natural compounds.

Divergent access to α-carbonyl-α′-vinyl sulfoxonium ylides and polysubstituted furans from β-ketosulfoxonium ylides and ynone-esters - Ingale, Sudhir R.; Sahu, Manas Ranjan; Borade, Balasaheb R.; Gamidi, Rama Krishna; Kontham, Ravindar (Journal of Organic Chemistry, 2025)
Here, we describe the synthesis of novel alpha-carbonyl-alpha `-vinyl sulfoxonium ylides under ambient, catalyst-free, and additive-free conditions, demonstrating broad substrate scope and scalability using beta-ketosulfoxonium ylides and alpha-ynone-esters. Furthermore, these ylides serve as versatile intermediates for the synthesis of highly substituted furans via Br & oslash;nsted acid (p-TsOH) catalysis at 130 degrees C. This approach offers key advantages, including wide substrate compatibility, divergent product formation from common precursors, gram-scale feasibility, and good to excellent yields.

Green one-pot three component synthesis of thiazolidine-2,4-dione based bisspirooxindolo-pyrrolidines with [Bmim]BF4: their in vitro and in silico anti-TB studies - Rukyanaik, V.; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (Molecular Diversity, 2025)
A simple and effective three-component one-pot green methodology was employed for the synthesis of a new thiazolidine-2,4-dione based bisspirooxindolo-pyrrolidine derivatives using [Bmim]BF4 ionic liquid via [3 + 2] cycloaddition reaction. It is an environmentally benign, column chromatography-free, shorter reaction time, good yield and easy product isolation method. The synthesized compounds 10a-x, were thoroughly characterized by using various spectroscopic methods like FT-IR, H-1 NMR, C-13 NMR, Mass spectrometry and finally by single crystal X-ray diffraction method. In vitro anti-tubercular (anti-TB) activity studies were carried out on these synthesized compounds, and they showed good to moderate anti-TB activity against Mycobacterium tuberculosis H37Rv strain. The compound 10a exhibited good anti-TB activity, with an MIC (Minimum Inhibitory Concentration) value of 12.5 mu g/mL, and the compounds 10m, 10o and 10r showed moderate activity with an MIC value of 25.0 mu g/mL. Remaining compounds exhibited poor activity against Mycobacterium tuberculosis. Ethambutol, rifampicin and isoniazid were used as standard drugs. Furthermore, in silico molecular docking experiments on the TB protein (PDB ID: 1DF7) were carried out to understand the binding interactions, and they showed least binding energy values ranging from -8.9 to -7.2 kcal/mol.
Keywords: 4-dione based bisspirooxindolo-pyrrolidines; Anti-TB activity; green synthesis; Molecular docking; Thiazolidine-2; [3+2] cycloaddition reaction; [Bmim]BF4

Palladium(II)-catalyzed desymmetrization of 2-alkynylbenzoate-tethered cyclohexadienones for the synthesis of polycyclic compounds - Rai, Archana; Bajpai, Priyam; Gamidi, Rama Krishna; Vanka, Kumar; Das, Utpal (Organic Letters, 2025)
Pd-catalyzed cascade cyclization of 2-alkynylbenzoate-tethered cyclohexadienone was developed for the single step synthesis of isocoumarin-fused dihydrochromenones. This highly atom economical method proceeds via 6-endo-dig cyclization of tert-butyl benzoate with a tethered alkyne. By modulating the reaction solvent and metal catalyst, the methodology was diverted for the purposeful synthesis of either of the E/Z tetra-substituted alkenes.

Sequential nitro-michael addition and reductive cyclization cascade reaction for diastereoselective synthesis of multifunctionalized 3,3′-pyrrolidinyl-spirooxindoles - Nichinde, Chandrakant B.; Bhati, Meema; Girase, Amardipsing S.; Patil, Baliram R.; Chaudhari, Suryakant S.; Gamidi, Rama Krishna; Joshi, Kavita; Kinage, Anil K. (European Journal of Organic Chemistry, 2025)
In this investigation, we elucidated, one-pot two stage efficient synthesis of multifuctionalized spiro[oxindole -3,3 `-pyrrolidine]. The methodology proceeds via organocatalyzed nitro-Michael addition reaction between indolylidenecyanoesters and nitroalkanes to formed nitro-Michael adduct which transformed into multifunctionalized 3,3 `-pyrrolidinyl-spirooxindoles by metal catalyzed reductive cyclization cascade. DFT investigations were conducted to elucidate the mechanism underlying the preferential reduction of the nitro group, with subsequent attack on the nitrile and ester groups remain inert throughout the reaction process. The approach is operationally simple, easily scalable, exhibits compatibility with readily accessible starting material and catalysts, thereby emphasizing cost-effectiveness.
Keywords: 3 `-pyrrolidinyl spirooxindoles; DFT study for regioselective cyclization; Diastereoselective 3; organocatalysis; Pd/C catalysed partial reductive spirocyclization

An ultrasound-assisted green synthesis of 1,3-diphenyl pyrazole-based spirooxindolo-1,2,4-oxadiazoles: their in vitro anti-tubercular activity and in silico molecular dynamics - Baddepuri, Sravanthi; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Gangarapu, Kiran; Basavoju, Srinivas (Chemistryselect, 2025)
A simple base-mediated one-pot synthetic green methodology has been successfully employed for the synthesis of 1,3-diphenylpyrazole-based spirooxindolo-1,2,4-oxadiazole derivatives. The newly synthesized analogues were tested for their in vitro anti-tubercular activity (anti-TB) against Mycobacterium tuberculosis H37Rv strain, and the results were reported as minimum inhibitory concentration (MIC) values ranging from 3.125 to 25 mu g/mL. Especially, the five compounds 3a, 3f, 3k, 3q, and 3v exhibited good to moderate anti-TB activity with MIC of 3.125 mu g/mL when compared to the reference drug ethambutol (MIC: 1.56 mu g/mL). In silico Molecular docking and molecular dynamics simulations of the protein-ligand complex (3a, 3f, 3k, and 3v) against Mycobacterium tuberculosis DprE1 (PDB ID: 5OEQ) of M. tuberculosis H37Rv strain revealed that these four compounds could be promising anti-mycobacterial candidates, as evident from the binding results and stability of the docked-ligand complexes with considerable least binding energies. ADME parameters were also studied to assess the drug likeness, which clearly shows that the newly developed compounds might be useful for the future development of novel anti-tubercular drugs.
Keywords: 1; 2; 4-oxadiazoles; In silico molecular dynamic studies; In vitro anti-tubercular activity; ultrasonication